1983
DOI: 10.1089/cdd.1983.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Intraarterial Cis-Platinum Chemotherapy for Patients with Primary and Metastatic Brain Tumors

Abstract: A total of 49 patients were treated using intraarterial cis-platinum infusions at a dose of 100 mg/m2. The patients were separated into three groups. There were 13 patients with metastatic tumors, 10 with recurrent malignant gliomas, and 22 patients with high-grade gliomas who received intraarterial cis-platinum as part of an adjuvant program. In addition, four nongliomatous primary brain tumors were treated in this fashion. Cis-platinum was filtered immediately prior to intraarterial infusion using a 0.22-mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…Selective IA administration of chemotherapeutics carries its own set of risks. Infra-ophthalmic carotid administration has been associated with CNS and retinal toxicity 14,15 , leukoencephalopathy 16 and deafness 17 . Headache, seizures, transient mental status changes, groin hematomas and urinary retention or incontinence have been reported 18 .…”
Section: Resultsmentioning
confidence: 99%
“…Selective IA administration of chemotherapeutics carries its own set of risks. Infra-ophthalmic carotid administration has been associated with CNS and retinal toxicity 14,15 , leukoencephalopathy 16 and deafness 17 . Headache, seizures, transient mental status changes, groin hematomas and urinary retention or incontinence have been reported 18 .…”
Section: Resultsmentioning
confidence: 99%
“…Kolaric et al [8] observed a complete response to intravenous CDDP treatment in one of eight patients, partial response in two, disease stabilization in one, and progression in four, that is, an overall a positive response rate of 3/8. Lehane and colleagues [17] reported a complete response to intra-arterial CDDP administration in one of eight patients, partial response in five, and no response in two, that is, an overall response rate of 6/8. Feun et al [18] reported a positive response in one of three patients given intra-arterial CDDR disease stabilization in one, and no response in one.…”
Section: Discussionmentioning
confidence: 98%
“…In general, the response of lung cancer to CDDP therapy seems to vary from case to case, depending on the sensitivity of the individual's cancer cells to this drug. Regarding chemotherapy of metastatic brain tumor derived from lung cancer, treatment with CDDP alone has been found to be efficacious in three separate studies [8,17,18]. Kolaric et al [8] observed a complete response to intravenous CDDP treatment in one of eight patients, partial response in two, disease stabilization in one, and progression in four, that is, an overall a positive response rate of 3/8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These tumors have demonstrated salutary response to cisplatin and doxorubicin therapy. 3 Intra-arterial delivery of chemotherapy is an accepted treatment for extremity osteosarcoma, [4][5][6] central nervous system tumors, [7][8][9][10] primary and metastatic liver [11][12][13] tumors, and breast cancer in selected patients. [14][15][16] The major advantage of intra-arterial drug infusion is the ability to administer a dose of therapeutic agent to the area of involvement through an undisturbed vascular system, resulting in a better therapeutic index ( Table 1).…”
Section: Methodsmentioning
confidence: 99%